PROTOTIPE ALAT PEMBERI PAKAN IKAN BERBASIS INTERNET OF THINGS - Wiwi, Muhammad hibrian; Isnandar, Dikki Prasetyo (Jurnal Ilmiah Teknologi Informasi Asia, 2024)
ABSTRACT. Aquaculture technology is growing rapidly to improve the efficiency of fish farming, including catfish feed. The purpose of this study is to create an automatic feeding system using an ESP32 microcontroller and servo motor, and controlled by the Blynk application. This system is expected to provide feed regularly, accurately, and reduce feed waste. It is hoped that this technology will help in better catfish farming, reduce waste, and increase feeding efficiency. The results of the study showed that this system had a 95% success rate in feeding. Although this system is effective, it is necessary to overcome the dependence on a stable internet connection and the durability of the servo motor. Overall, this study shows that the use of Internet of Things (IoT) technology in aquaculture can increase productivity and significantly benefit catfish farmers.